2012
DOI: 10.2478/v10078-012-0066-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic and aerobic performance of elite female and male snowboarders

Abstract: The physiological adaptation to training is specific to the muscle activity, dominant energy system involved, muscle groups trained, as well as intensity and volume of training. Despite increasing popularity of snowboarding only little scientific data is available on the physiological characteristics of female and male competitive snowboarders. Therefore, the purpose of this study was to compare the aerobic capacity and maximal anaerobic power of elite Polish snowboarders with untrained subjects. Ten snowboard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…Clearly, the impacts involved in P&P can be taxing, whilst activities such as “hiking the pipe” (walking up the side if lift cycles are too long, unavailable or inappropriate) at altitude can make training a physically demanding event. Most of the time though, when generally working with gravity rather than against it, P&P athletes’ energy expenditure and workload is comparatively low (e.g., Zebrowska et al, 2012 ). As this paper has suggested, however, the emotional challenge can be very high, especially when athletes are taking new tricks to snow for the first time.…”
Section: Practical Steps To Counter Negative Influencesmentioning
confidence: 99%
“…Clearly, the impacts involved in P&P can be taxing, whilst activities such as “hiking the pipe” (walking up the side if lift cycles are too long, unavailable or inappropriate) at altitude can make training a physically demanding event. Most of the time though, when generally working with gravity rather than against it, P&P athletes’ energy expenditure and workload is comparatively low (e.g., Zebrowska et al, 2012 ). As this paper has suggested, however, the emotional challenge can be very high, especially when athletes are taking new tricks to snow for the first time.…”
Section: Practical Steps To Counter Negative Influencesmentioning
confidence: 99%
“…Karakoç et al [ 19 ] have found in young soccer players significant negative relationships (–0.66) between peak power and FI measured in the Wingate anaerobic test and Yo-Yo intermittent recovery test level 2 performance. The study by Żebrowska et al [ 41 ] showed a significant negative correlation (–0.95) between relative peak power obtained from the Wingate test and O 2 max in female snowboarders.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are only two prior studies that have attempted to characterize physical attributes of elite snowboarders [6,7]. Our study attempted to build on these previous efforts as well address the call for further research by Ruotsalainen [18]; who indicated that research needs to be conducted in the areas of dynamic balance, speed, agility, and muscle power endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Common field tests were used to quantify parameters of physical fitness, as opposed to the previous research efforts [6,7] which relied upon laboratory based tests. We felt this was a strength of our study in that most coaches and athletes do not have access to research or performance labs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation